Answer:
see explanation
Step-by-step explanation:
the sum to n terms of an arithmetic sequence is
= [2a + (n - 1)d ]
where d is the common difference and a is the first term
here d = 9 - 7 = 7 - 5 = 2 and a = 5, hence
= [(2 × 5) + 2(n - 1) ]
= (10 + 2n - 2)
= (2n + 8)
= n² + 4n
When sum = 165, then
n² + 4n = 165 ← rearrange into standard form
n² + 4n - 165 = 0 ← in standard form
(n + 15)(n - 11) = 0 ← in factored form
equate each factor to zero and solve for n
n + 15 = 0 ⇒ n = - 15
n - 11 = 0 ⇒ n = 11
but n > 0 ⇒ n = 11
Answer:
a = 14
Step-by-step explanation:
3a = a + 28 ➡ 2a = 28 ➡ a = 14
Answer:
23
Step-by-step explanation:
The word decreased indicates the use of subtraction, so to figure out our answer we do the opposite, -1 + 24 = 23, after that we then subtract, 23 - 24 = -1, there for your answer should be 23 - 24 = -1, or more simply the number that has to be decreased to make the statement true is 23
#4(1)=-1. (2)=5. (3)=14. (4)=26 srry but all i know hoped i helped
[how i did]
the first one i did 3×-5+14 which equals -1
and the second one is the same two 3×-3+14=5 you just add the the number on B
Answer:
4,337 goes on top & 8 on the bottom
----------
8 & the answer is 542.12